2009
DOI: 10.1093/deafed/enp001
|View full text |Cite
|
Sign up to set email alerts
|

Toward an Equal Level of Educational Attainment Between Deaf and Hearing People in Sweden?

Abstract: Various educational reforms in Sweden have resulted in a formally equivalent educational system for deaf and hearing pupils. Has this resulted in equal levels of educational attainment? This article compares 2,144 people born between 1941 and 1980 who attended a special education program for the deaf and 100,000 randomly chosen individuals from the total population born between 1941 and 1980. Data consist of registered information about the individuals in the year 2005. Results demonstrate that the deaf popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 4 publications
2
18
0
Order By: Relevance
“…This national study found that a large disparity existed between deaf and hearing students regardless of educational placement. A similar disparity was found by Rydberg, Gellerstedt, and Danermark [190] across educational contexts. Svartholm [187], however, points to a different data set to argue for the positive impact of bilingual deaf education: the marked increase in the number of signing deaf adults attending Swedish universities.…”
Section: Is the Bimodal Bilingual Approach Effective?supporting
confidence: 82%
“…This national study found that a large disparity existed between deaf and hearing students regardless of educational placement. A similar disparity was found by Rydberg, Gellerstedt, and Danermark [190] across educational contexts. Svartholm [187], however, points to a different data set to argue for the positive impact of bilingual deaf education: the marked increase in the number of signing deaf adults attending Swedish universities.…”
Section: Is the Bimodal Bilingual Approach Effective?supporting
confidence: 82%
“…For some of the blind children, the segregation started even earlier when they were sent to orphanages at the age of three to five. Schools for the deaf were based on the 'oral method' and sign language was prohibited, which is something that seriously hampered the children's theoretical learning (see also Rydberg, Gellerstedt, and Danemark 2009). Several of the deaf interviewees said that they did not understand anything in school before they learned some sign language in the schoolyard, where older classmates could explain what was going on.…”
Section: Gradual Inclusionmentioning
confidence: 99%
“…With respect to education, it is known that deaf people in general have a lower level of educational attainment than hearing people in several countries (Anon 2006; Barnartt and Christiansen 1996;MacLeod-Gallinger 1992;Rydberg, Coniavitis Gellerstedt, and Danermark 2009). Higher education is generally demonstrated to have a positive effect on employment (Anon 2006;Welsh and Foster 1991;Welsh and MacLeod-Gallinger 1992;Winn 2007).…”
Section: Deaf People In Employmentmentioning
confidence: 99%